2022
DOI: 10.1155/2022/9390327
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Plasma Amino Acid Concentrations in Iranian Children with COVID-19

Abstract: COVID-19 is an acute viral disease that has so far infected more than 200 million and killed more than four million worldwide. It affects the immune system and other organs. Here, we investigated the level of free plasma amino acids in COVID-19 patients and compared them with non-COVID-19 subjects. We also compared amino acids levels in critically ill patients admitted to the intensive care unit (ICU) with non-ICU patients and expired and recovered patients. Twenty-six COVID-19 patients and 32 non-COVID-19 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Thus, it was shown that the level of blood serum L-Arg in patients with severe COVID-19 was significantly lower than that of patients with mild COVID-19 and the control group [ 161 , 162 , 163 ]. Moreover, a decline in L-Arg level was characteristic not only for adult patients, but also for children withSARS-CoV-2 infection [ 164 , 165 ].…”
Section: L-arginine Metabolism In Infectious Diseasesmentioning
confidence: 99%
“…Thus, it was shown that the level of blood serum L-Arg in patients with severe COVID-19 was significantly lower than that of patients with mild COVID-19 and the control group [ 161 , 162 , 163 ]. Moreover, a decline in L-Arg level was characteristic not only for adult patients, but also for children withSARS-CoV-2 infection [ 164 , 165 ].…”
Section: L-arginine Metabolism In Infectious Diseasesmentioning
confidence: 99%